The Studies of biological control of the tomato moth, a recent pest in Spain (Revista Científica Ciencias Naturales y Ambientales, 2015)
The hymenopteran parasitoids Apanteles gelechiidivoris and Necremnus artynes look promising among the diverse natural control agents of Tuta absoluta in Chile and Spain. In laboratory trials on disks of tomato leaflets, metaflumizone and flubendiamide were highly toxic for T. absoluta but innocuous for Necremnus. The insecticides imidacloprid and α-cypermethrin had low efficacy against T. absoluta, and were not compatible with the parasitoid. The braconid hymenopteran Apanteles gellechiidivoris should be included in similar studies, because of its role in natural control of T. absoluta in Colombia, its natural habitat, and northern Chile, and because of its potential use in Spain. Also, the toxicity of the insecticides used against pests should be analized continuously, to prefer those that affect the pest but are not so much toxic for natural enemies like N. artynes.
Keywords: Apanteles gelechiidivoris; biological control; Necremnus artynes; tomato moth; Tuta absoluta.